Antioxidative Self-Assembling Nanoparticles Attenuate the Development of Steatohepatitis and Inhibit Hepatocarcinogenesis in Mice - Takahisa Watahiki; Kosuke Okada; Ikuru Miura; Keii To; Seiya Tanaka; Eiji Warabi; Naomi Kanno; Kenji Yamagata; Naohiro Gotoh; Hideo Suzuki; Shunichi Ariizumi; Kiichiro Tsuchiya; et al. (MDPI AG, 2022)
Oxidative stress (OS) contributes to nonalcoholic steatohepatitis (NASH) and hepatocarcinogenesis. We investigated whether antioxidative self-assembling nanoparticles (SMAPoTN) could reduce the development of NASH and hepatocellular carcinoma (HCC) in p62/Sqstm1 and Nrf2 double knockout (DKO) mice and studied protective mechanisms. We measured disease development in male DKO mice fed a normal chow (NASH model) or a 60% high-fat diet (HFD; HCC model) with or without SMAPoTN administration for 26 weeks. SMAPoTN inhibited liver fibrosis in both groups and prevented HCC development (0% vs. 33%, p < 0.05) in the HFD group. SMAPoTN reduced OS, inflammatory cytokine signaling, and liver fibrosis. RNA-sequencing revealed that SMAPoTN decreased endoplasmic reticulum stress signaling genes in both groups, HCC driver genes, and cancer pathway genes, especially PI3K-AKT in the HFD groups. In the SMAPoTN treatment HFD group, serum lipopolysaccharide levels and liver lipopolysaccharide-binding protein expression were significantly lower compared with those in the nontreatment group. SMAPoTN improved the α-diversity of gut microbiota, and changed the microbiota composition. Oral SMAPoTN administration attenuated NASH development and suppressed hepatocarcinogenesis in DKO mice by improving endoplasmic reticulum stress in the liver and intestinal microbiota. SMAPoTN may be a new therapeutic option for NASH subjects and those with a high HCC risk.